2008
DOI: 10.1161/circulationaha.108.772715
|View full text |Cite
|
Sign up to set email alerts
|

Systems Approach to Understanding Electromechanical Activity in the Human Heart

Abstract: Abstract-The National Heart, Lung, and Blood Institute (NHLBI) convened a workshop of cardiologists, cardiac electrophysiologists, cell biophysicists, and computational modelers on August 20 and 21, 2007, in Washington, DC, to advise the NHLBI on new research directions needed to develop integrative approaches to elucidate human cardiac function. The workshop strove to identify limitations in the use of data from nonhuman animal species for elucidation of human electromechanical function/activity and to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 60 publications
0
54
0
Order By: Relevance
“…Electrical activation of myocytes initiates a number of ionic processes, which then culminate in mechanical contraction (13,16). Therefore, changes in the electrical activation pattern of the myocardium can alter the intracellular milieu of myocytes as well as the mechanical functioning of the affected myocardium (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical activation of myocytes initiates a number of ionic processes, which then culminate in mechanical contraction (13,16). Therefore, changes in the electrical activation pattern of the myocardium can alter the intracellular milieu of myocytes as well as the mechanical functioning of the affected myocardium (16).…”
Section: Discussionmentioning
confidence: 99%
“…Electrical activation of myocytes initiates a number of ionic processes, which then culminate in mechanical contraction (13,16). Therefore, changes in the electrical activation pattern of the myocardium can alter the intracellular milieu of myocytes as well as the mechanical functioning of the affected myocardium (16). Since a number of intracellular ions, e.g., Ca 2ϩ , play crucial roles as mediators/ activators in signaling cascades, and mechanical stretch can induce stretch-activated receptors, abnormalities in electrical activation may alter intracellular signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we have simplified the effect of mechanoelectrical feedback by only considering the effect of heart deformation to the position of electrical source. The realistic mechanoelectrical feedback simulation can only be achieved through models include the contribution of stretch-activated channels (SACs) [3,12]. However, this kind of models usually contain a lot of parameters and are much more complex than phenomenal models used in the paper.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical research has demonstrated that mechanical activity of the heart affects cardiac electrophysiology [3]. Mechanical activity affects cardiac electrophysiology mainly in two ways: firstly, the position of electrical source inside the myocardium will be changed while the geometry of the heart changes; secondly, stretch-activated ion channels in the cell membrane will be activated when the heart deforms [3,12]. In the paper, we only consider the effect of heart motion to the electrical source position.…”
Section: Mechanoelectrical Feedbackmentioning
confidence: 99%
“…During the last 20 years, such methods have made it conceivable to generate geometrically accurate numeric models that incorporate precise information about local cellular electrical activity, as well as highly sophisticated electrode and optical mapping systems that allow detailed analyses of the dynamics of cardiac electric wave propagation in 1, 2, and 3 dimensions in the normal and the disease heart. [10][11][12][13] Computational approaches have been used for many years as valuable tools to aid in research aiming at understanding…”
mentioning
confidence: 99%